An Unusual Stacking Transformation in Liquid‐Crystalline Columnar Assemblies of Clicked Molecular Propellers with Tunable Light Emissions. Issue 40 (14th August 2014) - Kim, Jinhee; Cho, Sung; Cho, Byoung‐Ki
Abstract The columnar liquid‐crystalline (LC) and fluorescence properties of three‐dimensional molecular propellers based on tetraphenylethylene is reported. X‐ray scattering studies reveal an unusual transition from a rectangular (Colrec) to a hexagonal columnar (Colhex) phase. In contrast to second‐order intercolumnar transitions based on a common tilt mechanism, the transition is first order and involves an unprecedented zigzag stacking of aromatic propellers in the Colrec phase. A sudden change in emission color from sky blue to green occurs rapidly and reversibly at this transition, which is due to the planarization of the propeller mesogen.